2005
DOI: 10.2169/internalmedicine.44.666
|View full text |Cite
|
Sign up to set email alerts
|

Infective Endocarditis and Acute Purulent Pericarditis in a Patient with Hyperglycemia

Abstract: A diabetic patient was admitted to our hospital for infective endocarditis with acute purulent pericarditis and diabetic ketoacidosis. Echocardiography revealed attachment of vegetation to the chordae tendineae in the left ventricle and pericaridial effusion. The vegetation was enlarged and pendulated for a few days despite maximal antimicrobial therapy. Surgical resection was desirable to decrease the risk of embolic complications and cardiovascular collapse. We could not open the heart because of accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The non-typical symptoms have been reported such as DKA associated with pericarditis and myocardial . However, the mechanism in the development of myocardial necrosis remains unclear [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The non-typical symptoms have been reported such as DKA associated with pericarditis and myocardial . However, the mechanism in the development of myocardial necrosis remains unclear [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Purulent pericarditis related to hyperglycaemia has been reported in some case reports [14][15][16][17], but there is a paucity of literature discussing purulent pericarditis related to diabetic ketoacidosis [14]. Purulent pericarditis related to hyperglycaemia has been reported in some case reports [14][15][16][17], but there is a paucity of literature discussing purulent pericarditis related to diabetic ketoacidosis [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, we believed the causes of severe bacteraemia and multi-site abscesses were related to the patient's immunocompromised condition of severe hyperglycaemia. Purulent pericarditis related to hyperglycaemia has been reported in some case reports [14][15][16][17], but there is a paucity of literature discussing purulent pericarditis related to diabetic ketoacidosis [14]. Oki et al [14] reported a case of a patient who had diabetic ketoacidosis complicated with infective endocarditis and purulent pericarditis and the latter was caused by spread of infection from the infective endocardium; however, the present case had a different pathogenesis and the most probable cause of multi-site abscess formation was hematogenous spread of oxacillin-sensitive Staphylococcus aureus infection from the right chest wall.…”
Section: Discussionmentioning
confidence: 99%
“…Noncardiac sources of renal artery emboli include thrombi on unstable aortic plaques, valvular vegetations in infective endocarditis, and paradoxical emboli in the setting of a patent foramen ovale. [6][7][8][9][10] The clinical presentation of RAE is variable, but most patients are in the sixth decade of life and complain of the acute onset of abdominal, flank, or back pain. The pain is typically constant and without significant modifying factors.…”
Section: Discussionmentioning
confidence: 99%